Exploring customer perceptions, knowledge, and challenges in participating in hibah: a case study at Maybank Lundang - Mahassan, Muthmainnah (2025)
Hibah is the transfer of ownership of property from one party to another without consideration, occurring during the donor's lifetime, sincerely and without coercion. Although it is considered a noble practice in Islam, hibah is less practiced in Malaysia due to a lack of knowledge and understanding. It not only transfers ownership but also avoids disputes among heirs after death. However, the rate of enforcement, subscription, and implementation of hibah in Malaysia is still low because many do not understand this concept. This study aims to explore customer perceptions, level of knowledge, and challenges faced in participating in hibah products. This research also assesses key factors such as religious awareness, perceived benefits, service quality, and trust in banking institutions, which influence customers' decisions to participate in hibah products at Maybank Lundang. The study uses a qualitative approach through face-to-face interviews with five Maybank Lundang customers, supported by document analysis and library research. Data were analyzed thematically and descriptively, with information organized to identify key factors. Record evaluation was also conducted to understand background issues and statistics from reliable sources to formulate more focused interview questions. The results of the study show that religious awareness, benefits of hibah such as flexibility and family harmony, quality of service, and belief in Shariah compliance play an important role in influencing the acceptance of hibah. This study suggests that financial institutions should improve their marketing strategies by emphasizing aspects of religious awareness, product benefits, and quality of service. This approach can increase the understanding and acceptance of hibah among the Muslim community in Malaysia, thus encouraging the implementation of hibah as a more widespread and efficient wealth planning instrument.